The Role of The Art Review in Shaping Urban Culture and Modernizing the Kingdom of Yugoslavia3 - Vukotić Lazar, Marta M.; Aleksić, Slađana V. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Milan Kašanin’s decisive initiative to launch The Art Review (1937–1941), the official journal of the Museum of Prince Paul, was pivotal in coordinating cultural and educational activities and played a key role in shaping and implementing cultural policy in the Kingdom of Yugoslavia. From its inaugural volume, the journal was guided by a meticulously conceptualized and systematically organized editorial, personnel, and financial policy. Managed as a professional, educational, popular, and propagandistic medium, The Art Review made an immeasurable contribution to the cultural development and social modernization of the Kingdom of Yugoslavia.This study examines the articles published in The Art Review from 1937 to 1941, focusing on architecture, urbanism, horticulture, interior design, and vernacular architecture, and analyzing their authors, who were predominantly architects. The aim is to elucidate the significance of this journal in interpreting the fundamental creative impulses of architectural practice, thereby facilitating the understanding of architecture as a discipline verging on the social and artistic. The architects who wrote for The Art Review, spearheaded by the editorial secretary Ivan Zdravković, included such prominent figures as Milan Zloković, Branislav Kojić, Aleksandar Deroko, Branislav Marinković, Branko Maksimović, Đurđe Bošković, Milutin Borisavljević, and others. These architects were both participants in and witnesses to a wide range of European intellectual movements at that time, while simultaneously acting as their advocates in this region. In this context, the paper discusses the issue of distinctive creative thinking on architecture from the perspective of Serbian and Yugoslav architects, focusing on two complementary components of creativity: the subjective (individual) and the collective (social), which, according to Kašanin, represents a higher level of understanding and appreciating architecture.
Keywords: The Art Review; art; culture; architecture; urbanism; society